P-032 Effect of defuse-3 and dawn trials on patient outcomes and stroke center volumes. (22nd July 2018) - Zhou, M; Kansagra, A
Abstract : Background and purpose: Recent results from DEFUSE-3 and DAWN trials support the use of endovascular thrombectomy (EVT) in selected patients beyond the conventional 6 hour time window. In this work, we estimate the impact of these trials on stroke center volumes and population-level clinical outcomes. Methods: In MATLAB 2017a Simulink, we simulated extending EVT eligibility in a system comprising one primary stroke center (PSC) and one comprehensive stroke center (CSC), using three different routing paradigms. In the Nearest Center paradigm, patients are initially sent to the nearest center regardless of capability, while in EVT First, patients are sent to the nearest EVT-capable center. In Rhode Island, patients with FAST-ED ≥4 are sent to an EVT-capable center, while the others are sent to the nearest center. Good clinical outcome, defined as mRS 0–2, is determined by type and timing of treatment using associated clinical trial data. Results: In both EVT First and Rhode Island paradigms, extending the EVT time window increases patients receiving EVT from 40.1% to 50.2%, a relative increase of 25.0%, and increases good clinical outcomes from 43.0% to 43.8%. In the Nearest Center paradigm, extending the EVT time window increases patients receiving EVT from 39.8% to 49.9%, a relative increase of 25.4%, and increases good clinical outcomes from 42.0% to 42.7%. Conclusion: Extending the EVT time window in accordance with DEFUSE-3 and DAWN trial criteria increases the volume of EVT by approximately 25% and modestly improves population-level clinical outcomes. Disclosures: M. Zhou: None. A. Kansagra: None.